Preparation of oat galactolipid and anti-liver cancer effects of oat galactolipid–modified curcumin-loaded liver targeting vesicle - Ren, Huiying; Chen, Nuo; Liu, Yanqing; Wu, Meimei; Yan, Jingsong; Chang, Mingxiang; Li, Hanmin (Frontiers in Pharmacology, 2025)
IntroductionThe mortality rate for liver cancer is extremely high but clinical treatments have not made much progress, so it is necessary to develop anticancer agents with lower toxicities and more effective liver-targeting drug delivery systems (LTDDSs). At present, LTDDSs mediated by the asialoglycoprotein receptor (ASGPR) show excellent effects at improving the liver-targeting and antitumor effects of drugs. However, the galactosyl ligands are typically prepared by chemical synthesis and have some shortcomings. The present work endeavors to explore the influences of plant galactolipids as natural galactosyl ligands for LTDDSs.MethodsPlant galactolipids were extracted from oat bran, and their characteristics were tested. Then, oat-galactolipid-modified curcumin-loaded liver-targeting vesicles (GCLTVs) and curcumin-loaded vesicles were prepared, which were used in a comparative study of the liver-targeting and liver anticancer effects in vitro and in vivo.ResultThe experimental results show that the oat galactolipids and GCLTVs were prepared successfully. The hydrophilic–lipophilic balance, acid, ester, and saponification values of the oat galactolipids were 14.89, 47.22, 237.09, and 284.30, respectively. The morphology of the GCLTV was spherical, with an average particle size of 64.47 nm and average potential of −19.73 mV. The optimal proportion of galactolipids in the GCLTVs was selected as 30%. Compared with the curcumin-loaded vesicles, GCLTV uptakes were significantly higher at 1, 2, and 4 h; further, the galactolipid modification significantly improved the liver-targeting capability of the GCLTVs in vivo. The inhibitory effects of the GCLTVs on the proliferation of HepG2 cells were significantly higher than those of the curcumin-loaded vesicles after 24 and 48 h. The antitumor effects of GCLTVs in vivo based on H&E staining results on liver tissues were stronger than those of the curcumin-loaded vesicles, and the expressions of P53, Bcl-2, and Bax were correspondingly more significant.ConclusionThe GCLTVs show excellent liver-targeting capabilities in vitro and in vivo. Compared to the curcumin-loaded vesicles, the cytotoxicity and anticancer effects of the GCLTVs were significantly higher in vitro and in vivo. Thus, oat galactolipids could be used as a type of natural ligand of the ASGPR and a membrane material that would be beneficial for liver-targeting nanopreparations.